Comparative Quantitative Visual Improvement in Endoscopic Endonasal Transphenoidal Versus Transcranial Resection of Pituitary Adenoma - Irshad, Aamir; Mian Iftikhar Ul Haq (Indus Journal of Bioscience Research, 2025)
Introduction: Pituitary adenomas are common benign tumors arising from the anterior pituitary gland, accounting for approximately 10–15% of intracranial neoplasms. Objective: To compare the quantitative visual improvement achieved using the endoscopic endonasal approach vs open transcranial approach performed for pituitary adenoma surgery performed in neurosurgery department of Hayatabad Medical Complex MTI hospital Peshawar. Material and Methods: This Randomized control trial was conducted at Neurosurgery department, HMC Hospital Peshawar during 26 October 2024 to 25 Feb 2025. Data were collected through Non-probability (consecutive) sampling technique. A total of 76 patients diagnosed with pituitary adenomas were randomized into two groups (A and B) of 38 patients each. Group A underwent the endoscopic endonasal approach, while Group B underwent the transcranial approach. Results: Visual improvement was significantly higher in Group A (84.2%) compared to Group B (57.9%) (p = 0.01). The mean surgery duration was shorter in Group A (150 ± 20 minutes) than in Group B (180 ± 25 minutes) (p = 0.01). Postoperative complications were observed in 10.5% of Group A and 26.3% of Group B (p = 0.04). Patient satisfaction scores were also higher in Group A (8.5 ± 1.2) compared to Group B (7.0 ± 1.5) (p = 0.02). Conclusion: It is concluded that the endoscopic endonasal approach offers superior visual outcomes, shorter operative times, and fewer complications compared to the transcranial approach. These findings support the adoption of the minimally invasive endoscopic technique as the preferred surgical method for pituitary adenoma resection, with the transcranial approach reserved for specific complex cases. Further studies are needed to evaluate long-term outcomes and applicability to a broader patient population.